Description of two new species in the Ixodes ricinus complex from the New World (Acari: Ixodidae), and redescription of Ixodes affinis Neumann, 1899 - Nava, Santiago; Beati, Lorenza; Venzal, Jose M.; Durden, Lance A.; Bermudez, Sergio E.; Tarragona, Evelina L.; Mangold, Atilio J.; Gleason, Debbie; Mastropaolo, Mariano; Guglielmone, Alberto A. (Zootaxa, 2023)
Ixodes chacoensis n. sp. is described based on males, females, nymphs and larvae collected from vegetation, ungulates and passerine birds in northeastern Argentina. Ixodes affinis Neumann, 1899 is redescribed based on the original type specimens (females) from Leopardus pardalis, and from recently collected specimens from Costa Rica. Ixodes keiransi n. sp., previously treated as North American populations of Ixodes affinis, is described based on males and females from carnivores and ungulates from the southeastern United States. Concatenated total evidence phylogenetics based on combined DNA sequence analyses from mitochondrial genes (12SrDNA, 16SrDNA and COI) and a nuclear gene (ITS2) corroborate the recognition of these species.